Comparative study of material loss at the taper interface in retrieved metal-on-polyethylene and metal-on-metal femoral components from a single manufacturer. (August 2017) - Bills, Paul; Racasan, Radu; Bhattacharya, Saugatta; Blunt, Liam; Isaac, Graham
There have been a number of reports on the occurrence of taper corrosion and/or fretting and some have speculated on a link to the occurrence of adverse local tissue reaction specifically in relation to total hip replacement which have a metal-on-metal bearing. As such a study was carried out to compare the magnitude of material loss at the taper in a series of retrieved femoral heads used in metal-on-polyethylene bearings with that in a series of retrieved heads used in metal-on-metal bearings. A total of 36 metal-on-polyethylene and 21 metal-on-metal femoral components were included in the study all of which were received from a customer complaint database. Furthermore, a total of nine as-manufactured femoral components were included to provide a baseline for characterisation. All taper surfaces were assessed using an established corrosion scoring method and measurements were taken of the female taper surface using a contact profilometry. In the case of metal-on-metal components, the bearing wear was also assessed using coordinate metrology to determine whether or not there was a relationship between bearing and taper material loss in these cases. The study found that in this cohort the median value of metal-on-polyethylene taper loss was 1.25 mm 3 with the consequent median value for metal-on-metal taper loss being 1.75 mm 3 . This study also suggests that manufacturing form can result in an apparent loss of material from the taper surface determined to have a median value of 0.59 mm 3 . Therefore, it is clear that form variability is a significant confounding factor in the measurement of material loss from the tapers of femoral heads retrieved following revision surgery.